Voltage-Dependent Photoluminescence and How It Correlates with the Fill Factor and Open-Circuit Voltage in Perovskite Solar Cells - Stolterfoht, Martin; Le Corre, Vincent Marc; Feuerstein, Markus; Caprioglio, Pietro; Koster, L Jan Anton; Neher, Dieter (ACS Energy Letters, 2019)
Optimizing the photoluminescence (PL) yield of a solar cell has long been recognized as a key principle to maximize the power conversion efficiency. While PL measurements are routinely applied to perovskite films and solar cells under open circuit conditions (V-OC), it remains unclear how the emission depends on the applied voltage. Here, we performed PL(V) measurements on perovskite cells with different hole transport layer thicknesses and doping concentrations, resulting in remarkably different fill factors (FFs). The results reveal that PL(V) mirrors the current-voltage (JV) characteristics in the power-generating regime, which highlights an interesting correlation between radiative and nonradiative recombination losses. In particular, high FF devices show a rapid quenching of PL(V) from open-circuit to the maximum power point. We conclude that, while the PL has to be maximized at V-OC at lower biases < V-OC the PL must be rapidly quenched as charges need to be extracted prior to recombination.